Azuzadores y desacuerdos morales - Suarez, Pyro (2023)
In the protests carried out during 2022 and 2023 in Peru, the majority of the press pointed out the presence of protest fomenters playing a significant causal role in the participation of the other protesters. On the other hand, empirical evidence about our intuitions on moral disagreements (Khoo Knobe 2018) seems to suggest that the difference in cultural background of the disagreeing parties plays a role in our perception of whether both parties are holding something correct in their own terms. In this article, I argue that to propose a specific kind of protest fomenters has the communicational effect of ruling out the option of thinking of the participants of the conflict as holding something correct at the same time.